FAKTOR â FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN MAKANAN PADA SISWA SEKOLAH MENENGAH ATAS DI KOTA YOGYAKARTA - , INDIRA PUTUAYU SEPTIANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The problem of nutrient intake in teenager stends to be caused by a poor and irregular diet as well as psychosocial factors involved frequently become the cause of this matter.There are research studies indicating that there are changes in food selection, from childhood to adolescence, such as decreases in the consumption of vegetables and fruits, and increases in high-fat food consumption. The stage of food selection among the teenagers is very important to note, since they begin to step on independence stage, involving their surrounding social environment. Objective: This research is aimed to determine the factors associated with food selection in high school students in Yogyakarta City Methods: The design of this research was observational, with crosssectional design on 2 high schools in Yogyakarta City. The sampling was done by simple random sampling. A sample of 107 students was examined as the sample. The variable examined in this research was the role of the family, peers,pocket money, the level of knowledge and mood towards food selection. The data were analyzed by using chi-square. Results: Factors significantly related (p <0,05) to the food selection is the role of the family in the selection ofstaple foods, side dishes from animal products, side dishes from vegetables, vegetables and fruits. The significant relationship is also found at the level of knowledge with food selection of vegetables and fruits. In addition, a significant relationship between mood and selection of staple foods and side dishes from animal products is also found. Meanwhile, there is no significant relationship between pocket money and the role of peers towards all types of food selection. Conclusion: The role of the family, the level of knowledge and mood are related to food selection, while pocket money and peersare not related to food selection.